The Contribution of Islamic Financial Instruments to Maritime Development: Evaluation and Policy Recommendation for Maluku Regions - Shalihah, Mar'atun; Yarusain Amin, Deny; Yaman, Afdhal; Husen Sobana, Dadang; Syarif, Abdul Rilan (Sekolah Tinggi Agama islam Negeri Majene, 2025)
Maritime development in the Indonesian archipelago faces structural challenges, particularly in obtaining inclusive, sustainable, and locally suitable funding in Maluku. To address these issues, Islamic financing system is considered as a potential alternative to conventional system, using instruments based on Maqasid al-sharia principles. This study aims to evaluate five Islamic financial instruments focusing on productive Waqf, Mudharabah, Ijarah, Musyarakah, and Sukuk, in supporting the development of maritime regions in Maluku. We used MCDA with AHP and TOPSIS methods to evaluate these instruments. The evaluation criteria were economic feasibility, Sharia compliance, risk management, social support, and environmental impact. The results rank instruments, with productive Waqf being the most effective, followed by Mudharabah, Ijarah, and then Musyarakah and Sukuk being less suitable. The study reveals that productive Waqf is at the top due to its non-commercial nature, community participation, and reaching marginalised groups. Mudharabah is considered good for micro and small businesses with profit-sharing. Ijarah is for financing assets without ownership transfer. Musyarakah and Sukuk are less flexible for coastal communities. The findings of this study highlight that Islamic financing systems have an essential role in guiding decision-making in the maritime development.